2018
DOI: 10.1186/s12877-018-0967-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of frailty by frailty phenotype in rural Tanzania

Abstract: BackgroundThe frailty phenotype is defined by the presence of three from the following five clinical features: weakness, slow walking speed, unintentional weight loss, exhaustion, and low physical activity. It has been widely applied in different research and clinical contexts, including across many low and middle-income countries. However, there is evidence that the operationalisation of each component of the frailty phenotype significantly alters its characteristics and predictive validity, and care is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 36 publications
5
42
1
2
Order By: Relevance
“…In accordance with previous studies (Lewis et al, 2018), our findings revealed a high number of women and widow(ed) participants. The education level among this group is very low (or inexistent), which is why we considered participants who were illiterate versus those who attended school for 1 year or more.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous studies (Lewis et al, 2018), our findings revealed a high number of women and widow(ed) participants. The education level among this group is very low (or inexistent), which is why we considered participants who were illiterate versus those who attended school for 1 year or more.…”
Section: Discussionsupporting
confidence: 93%
“…Frail individuals represented more than two-thirds of the total sample (71.8 vs. 24.6% of prefrail). These results are in accordance with other studies (Duarte and Paúl, 2015;Lewis et al, 2018), which also had a great number of frail oldest old individuals in their samples, highlighting the low differentiation (almost all frail persons) provided by the frailty phenotype of Fried among oldest old individuals and emphasizing the need to better understand its components.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The population-based lowest 20% of the handgrip strength, gait speed, and physical activity need to be calculated based on the population distributions. Calculation of the Frailty Index requires the recording of various types of deficits (typically more than [30][31][32][33][34][35][36][37][38][39][40] and dividing the number of deficits present by the number of deficits considered, which may take ~20-30 minutes, 19 Kojima et al…”
Section: Definition Of Frailtymentioning
confidence: 99%
“…28 A higher prevalence of frailty is also observed in selected populations with specific diseases or conditions, such as patients with cancer (42%), 29 end-stage renal disease (37%), 30 heart failure (45%), 31 Alzheimer disease (32%), 32 and nursing home residents (52%). 33 Although the mean prevalence of frailty gradually increases with age, 28,[34][35][36][37] the individual course of frailty varies and the level of frailty can be reduced even in old age. 4,38 Several longitudinal population-based studies have showed that 8.3%-17.9% of older adults actually improved their frailty status [39][40][41][42][43][44] and that some of them made frequent and dynamic transitions over time.…”
Section: Prevalence and Natural Course Of Frailtymentioning
confidence: 99%